An analysis of the income tax consequences attendant upon the transfer of contingent liabilities in the sale of a business as a going concern - Hansraj, Shivona (My University, 2017)
The transfer of contingent liabilities as part of a sale of business transaction has always been a contentious issue. In particular, there is still a measure of uncertainty in whose hands, if any, contingent liabilities transferred as part of a sale of business may be deductible. Sale of business agreements may be structured in various ways, for example, the purchaser may acquire the seller’s business in exchange for cash, the creation of a loan account, or the assumption of liabilities. Furthermore, in the context of intra-group transactions to which the group roll-over relief provisions apply, the Income Tax Act 19621 (‘the Income Tax Act’) does not specifically address the transfer of contingent liabilities. This research report addresses the income tax consequences arising from the transfer of contingent liabilities from the seller to the purchaser, including an analysis of the relevant group roll-over relief provisions. Key words: Ackermans Judgment, Actually Incurred, Contingent Liabilities, Free-standing Contingent Liabilities, General Deduction Formula, Group roll-over relief, Interpretation Note 94, Sale of Business Transaction, SARS.
A research report submitted to the Faculty of Commerce, Law and Management in fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation), 13 September 2017
Online resource (iii, 61 leaves)
Keywords: Business enterprises--Purchasing--Law and legislation--South Africa; Sale of business enterprises--Law and legislation--South Africa; Tax accounting--South Africa